Special Methods and Sources of Interpretation in Tafsir Al-Madzhari (Analysis of Surat Ad-Dhuha) - Tasya Putri Nurhayat; Novi Nur Sholihat; Eni Zulaiha; Wildan Taufiq (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Throughout Islamic history, there have been interpretations of the Qur'an that, instead of explaining Islamic law, have caused divisions among the people and even led to misunderstandings of Islamic teachings themselves. If examined further, the problem is caused by interpretations of the Qur'an in a way that deviates from the correct method and authentic sources. Seeing how important it is to know the methods and sources of interpretation in interpreting the Qur'an, this paper aims to discuss the specific methods and sources of interpretation, specifically in Tafsir Al-Madzhari by Qadi Muhammad. The approach used is a qualitative approach using a literature review in collecting data. The results of this study include: First, Qadi Muhammad Thanaullah Panipati was born in the city of Panipati. He is an expert in Fiqh and Hadith. Second, Qadi Muhammad's specific method in interpreting the Qur'an in Surah Ad-Dhuha is (1) mentioning the name of the surah at the beginning of the interpretation. (2) mentioning the type of surah (Makiyah/Madaniyah) and the number of verses in the surah. (3) including all verses from the surah being interpreted. (4) interpreting the Qur'an by explaining the reasons for the revelation of a letter or verse. (5) paying attention to the degree of hadith. (6) writing down the verse before interpreting it. (7) including the vocabulary or meaning of the verse. (8) interpreting using the rules of I'rab of the Qur'an. (9) using the munasabah of verses in interpreting the Qur'an. (10) explaining the meaning with the help of poetry. (11) mentioning the differences in Qira'at in the letter being interpreted. (12) mentioning the problems of fiqh. Third, the primary sources of interpretation in Al-Madzhari's interpretation of the Ad-Dhuha letter are eleven verses of the Qur'an without narrations, 23 Hadith of the Prophet, 15 Qaul Tabi'in. While the secondary sources of Al-Madzhari's interpretation of the Ad-Dhuha letter are four language rules, six sayings of the mufassirin and sufis, and one Arabic poem. Fourth, if viewed from the source of the interpretation, Al-Madzhari's interpretation falls into the category of interpretations based on the interpretations of the narrations (tafsir bil ma'tsur) because the narrations are more dominant than reason. Meanwhile, if we look at the tsaqafah and hadf mufassir, this interpretation is of a fiqh nature, because in addition to being a judge, he was also an expert in fiqh and hadith.